2014
DOI: 10.9755/ejfa.v26i9.18122
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of thermotolerant and high acetic acid-producing Acetobacter pasteurianus from Ivorian palm wine

Abstract: The aim of this work was to identify acetic acid bacteria expressing technological characteristics for further use in vinegar production in tropical countries. It was focused on isolation and identification of thermotolerant acetic acid bacteria strains from Elaeis guineensis wine of Côte d'Ivoire (Ivorian palm wine). A screening was performed to find out strains with high vinegar production, tolerant against high ethanol, acid and sugar concentrations as well as tolerating high production temperatures. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…For instance, Lu et al [30]reported an acidproducing Acetobactersp strains from spoiled banana in Taiwan, with short lag phase (12 h). Furthermore, no lag phase for acid production was observed in Acetobacterpasteurianus strains isolated from palm wine [29] and traditional rice fermentation [22].The long lag phase observed in our AAB strains studied, may be indicative of their behavior in their natural ecosystem (cocoa fermentation) and seems to be a common property for AAB involved in cocoa fermentation since Romero-Cortes et al [27]also reported a long lag phase (2 days) in AAB strain Acetobactertropicalis from Mexican cocoa fermentation. In fact, maximum production of acetic acid during cocoa fermentation occurs generally after the third day [7,25]and AAB strains should keep a low level of acid production until this period which corresponds to the occurrence of reactions leading to formation of cocoa and chocolate aroma precursors.…”
Section: Screening Of Producing Aab Strainsmentioning
confidence: 47%
See 1 more Smart Citation
“…For instance, Lu et al [30]reported an acidproducing Acetobactersp strains from spoiled banana in Taiwan, with short lag phase (12 h). Furthermore, no lag phase for acid production was observed in Acetobacterpasteurianus strains isolated from palm wine [29] and traditional rice fermentation [22].The long lag phase observed in our AAB strains studied, may be indicative of their behavior in their natural ecosystem (cocoa fermentation) and seems to be a common property for AAB involved in cocoa fermentation since Romero-Cortes et al [27]also reported a long lag phase (2 days) in AAB strain Acetobactertropicalis from Mexican cocoa fermentation. In fact, maximum production of acetic acid during cocoa fermentation occurs generally after the third day [7,25]and AAB strains should keep a low level of acid production until this period which corresponds to the occurrence of reactions leading to formation of cocoa and chocolate aroma precursors.…”
Section: Screening Of Producing Aab Strainsmentioning
confidence: 47%
“…This production is particularly higher than that from AAB in Mexican cocoa fermentation reported by Romero-Cortes et al [27]which was 25 g/L. However, Sharafi et al [28] isolated AAB(Acetobacterpasteurianus) from fruit with capacity to produce up to 100 g/L of acetic acid while Konaté et al [29]reported AAB(Acetobacterpasteurianus) as the best acid producer from traditional palm wine producing 30 g/L of acetic acid. At date, the strain 121D isolated in this study, present the higher acetic acid production from cocoa fermentation.…”
Section: Screening Of Producing Aab Strainsmentioning
confidence: 82%
“…The characteristics of LKN6 isolate which are ethanol and sugar tolerant indicated that isolate LKN6 is able to produce acetic acid. Konate et al (2014) stated that the AAB that are tolerant to high ethanol and sugar concentrations have the ability to produce acetic acid.…”
Section: Identification Of the Best Bacterial Cellulose Producermentioning
confidence: 99%
“…According to [17], A. aceti subspecies aceti is capable of producing AA at 37 • C after a three-day lag phase of production. Other authors have isolated strains of A. pasteurianus from palm wine, Cacao and apple that are capable of producing AA at 39 • C [22], at 47 Tolerance in AAB to high temperatures can be achieved by thermal adaptation of the isolated strains. This thermal adaptation plays an important role not only in the reduction of the cooling system, but also in the protection of the fermentation process against accidental failures of the thermal management [24].…”
Section: Introductionmentioning
confidence: 99%